The Development of a CRISPR-Cas9 Gene Editing Platform to Efficiently Deliver HPV Neoantigen-Specific T Cell Receptors to Cytotoxic CD8+ T Cells - Anderson, Abby (My University, 2024)
HPV-related cancers remain prevalent worldwide despite the development of several efficacious vaccines. Fortunately, the unique expression of E6 and E7 proteins allows for the specific targeting of HPV cancer cells by engineered immune cells with binding specificity to these antigens. The Heath lab is generating a methodology for the treatment of HPV-16 related cancer using TCR-engineered cytotoxic T cell immunotherapy. This lab-wide initiative involves the discovery of TCRs from HPV-16 cancer patient blood samples, TCR assembly, and preclinical functional validations. The non-viral gene editing system CRISPR-Cas9 is used to generate these engineered T cells, whose simplicity and safety allows for the generation of many T cell clones expressing several patient-specific TCR sequences. My role in this project was to first improve the efficiency of CRISPR-Cas9 gene editing of T cells using experimental methods, and to apply this strategy towards the development of HPV-specific CD8+ T cells. Using various methodologies, the CRISPR-Cas9 knock-in efficiency was increased from 0.1% to 10%. This improved method was used to investigate HPV-specific TCR sequences in both Jurkats and primary human T cells, where TCRs 001-006 showed adequate cell surface expression. Unfortunately, these TCRs did not demonstrate functionality in cytokine release assays in primary T cells. However, future TCRs with adequate expression and function will be used in a clinical trial to test the ability of a multiplexed TCR-engineered T cell immunotherapy to have improved clinical outcomes compared to a therapy using a single known T cell clonotype.
Thesis (Master's)--University of Washington, 2024
Keywords: ACT; CRISPR-Cas9; Genetic engineering; HPV; T cell; TCR-engineered T cell therapy; Bioengineering; Immunology; Genetics; Bioengineering